An unusual Northwest–Southeast oriented Meiyu rain belt in 2021 - Huo, Liwei; Guan, Zhaoyong; Zhang, Mengke; Jin, Dachao; Wang, Ji; Shi, Yinglong; Wang, Yi; Liu, Yin; Liu, Chun (Frontiers in Earth Science, 2023)
Affected by the East Asian summer monsoon, summer floods occur frequently in eastern China, causing huge economic losses and social impacts. In 2021, the precipitation anomaly during the Meiyu period in Yangtze-Huaihe River Valley (YHRV) was abnormally high, with the value of 188.0 mm, about 1.7 times the standard deviation. However, it did not cause serious flood disaster. This was mainly due to the existence of two precipitation anomaly centers in YHRV, which shared the impact caused by the excessive precipitation. These two centers were located at the junction of Anhui and Henan provinces and at the junction of Jiangsu, Anhui and Jiangxi provinces, respectively. Positive precipitation anomalies were distributed in a northwest-southeast oriented band. During the 2021 Meiyu period, the intensity of the western Pacific subtropical high (WPSH) was weaker and extended further westward. And an anticyclonic circulation anomaly in the lower troposphere was over the eastern China. This was related to the quasi-stationary wave train propagating eastward from Hainan Island to the northwestern Pacific, in which the Rossby wave source term plays a major role. In addition, the tropical Atlantic anomalous warming caused anomalous convergence of the upper troposphere in the eastern Mediterranean through a monsoon-desert-like teleconnection and excited quasi-stationary wave trains in the upper layers propagating downstream along the mid-latitudes, enhancing the geopotential height in eastern China and thus favoring the westward extension of WPSH. These leaded to anomalous easterly winds along the eastern coast of China and anomalous southwesterly winds from Guangxi province to the middle and lower reaches of the Yangtze River. Similar anomalous transport of water vapor also existed and converges in the YHRV. The above-mentioned reasons have jointly caused the abnormally high total precipitation and the atypical spatial distribution of precipitation in 2021 Meiyu season. The research results can provide scientific basis and clues for understanding Meiyu anomalies and disaster prevention and mitigation